Studying binary clathrate hydrate of hydrogen and deuterium using raman spectroscopy - El.Ghazaly, Moaaz (AUC Knowledge Fountain, 2014)
In the scene of the increasing global need to find a good manner to use hydrogen as a source of energy; this research stand as one of the promising methods to do so. Clathrate hydrates show a possible material to store hydrogen which is a clean fuel and exist in nature in large quantities at different places. Clathrate hydrates are crystalline molecules with shape like ice, but have different crystal structure. Simply, applying high pressure and low temperature on water molecules will form Clathrate hydrate which represents a phase transition from water. About 6.4 trillion tones of methane-hydrates are found to be deep on ocean floor, which represent a significant source of energy just requires an efficient and economic method to be used. Besides the importance of clathrates in terms of energy demands, this research participates in increasing the knowledge of fundamental physical and chemical processes in one of the important international research topics. Raman spectroscopy has been performed on different samples of binary Clathrate hydrate of hydrogen and deuterium. Actually, we used Raman Spectroscopy because it is a powerful tool for investigating the molecular dynamics of the guest molecule inside the clathrate cages, in addition to estimating the occupancy number of molecules per cage. The experimental part of this thesis was done at CNR, Florence, Italy, while the data analysis was carried out at Physics department, The American University in Cairo in the scene of scientific collaboration between the two institutions.